2020
DOI: 10.1186/s12920-020-0660-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of inflammatory bowel disease-associated miRNAs using a novel bipartite clustering approach

Abstract: Background: Multidimensional data mining from an integrated environment of different data sources is frequently performed in computational system biology. The molecular mechanism from the analysis of a complex network of gene-miRNA can aid to diagnosis and treatment of associated diseases. Methods: In this work, we mainly focus on finding inflammatory bowel disease (IBD) associated microRNAs (miRNAs) by biclustering the miRNA-target interactions aided by known IBD risk genes and their associated miRNAs collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 55 publications
(56 reference statements)
1
15
0
Order By: Relevance
“…Specifically, they found that let-7c may be highly related to IBD due to number of relevant miRNA-target interactions. 30 The miRNA let-7c also promotes M2 macrophage polarization (anti-inflammatory) and suppresses M1 (pro-inflammatory) polarization. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they found that let-7c may be highly related to IBD due to number of relevant miRNA-target interactions. 30 The miRNA let-7c also promotes M2 macrophage polarization (anti-inflammatory) and suppresses M1 (pro-inflammatory) polarization. 31 …”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, the research field of miRNAs in IBD has grown rapidly after their discovery. Several studies have found significantly different profiles of hundreds of miRNAs 20 , 38 between IBD and healthy individuals, 39 paediatric and adult patients, 40 inflamed and non-inflamed mucosa, and in relation to disease activity. 15 , 35 , 37 , 40 To date, there are enough collected data to say that miRNAs are important regulatory factors that play a relevant role in the pathogenesis of IBD.…”
Section: The Relevance Of Mirna In Ibd Pathogenesismentioning
confidence: 99%
“…Additionally, a recent meta-analysis used a novel bipartite approach to find miRNA associated with IBD. 38 Among the most relevant was the Let-7 family. This is a multifaceted family of miRNA highly conserved across diverse animal species and related with cell proliferation, cell cycle, metabolism, and cell migration.…”
Section: The Relevance Of Mirna In Ibd Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), is a frequent gastrointestinal disease worldwide, which can affect any part of the digestive tract [ 1 ]. Epidemiological evidence indicates that the rate of IBD is increased every year, and there is currently no specific treatment for this disease [ 2 ]. IBD pathogenesis is a result of the interplay between environmental, genetic and immune response factors.…”
Section: Introductionmentioning
confidence: 99%